Early results of the novel radiofrequency balloon ablation catheter for pulmonary vein isolation. (19th May 2022) - Breitenstein, A; Kanthasamy, V; Hofer, D; Hunter, R; Butcher, CH; Ahluwalia, N; Schilling, RJ; Finlay, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) remains the cornerstone for treating of symptomatic atrial fibrillation (AF). Single-shot PVI technologies have evolved as a standard for first-time PVI. A novel radiofrequency balloon ablation catheter is now available to offer single-shot RF pulmonary vein isolation. Purpose: To summarize the early experience using the novel RF balloon ablation catheter for patients undergoing PVI in two tertiary centres in Europe. Methods: We prospectively assessed the first 38 consecutive patients undergoing PVI using RF balloon ablation catheter for paroxysmal or persistent AF in two high volume centres. Both centres used a standardised approach including ultrasound-guided vascular access, uninterrupted anticoagulation, transeptal puncture via the RF balloon sheath and a limited 3D mapping software-guided LA geometry created with a circular mapping catheter. Radiofrequency application for 60s to the anterior segments and 20s posteriorly was performed in all cases, phrenic pacing was employed for ablation of right PVs. BHS performed all procedures (except 2 cases due to high BMI and severe sleep apnea) under sedation, while all patients from UHZ underwent PVI procedures with general anaesthesia as per institutional protocol. All patients had an oesophageal temperature probe to assess oesophageal temperature during ablation (passed orally under sedation) and had uninterrupted oral anticoagulation throughout the periprocedural period. Results: Overall, mean age was 64±8 years, 23 (61%) were male, 24 (63%) of patients had paroxysmal AF. The majority were de novo interventions (92%). There was no significant difference between the patients demographics in the two hospitals. All veins were isolated in both groups with a total of 144 applications (n = 73 in the sedation group, n = 71 in the GA population). Median fluoroscopy time was comparable (sedation group 1.1 minutes vs GA group 1.2 minutes; P = 0.58), but median procedure time was shorter in the sedation group (65 minute vs 106 minutes; P < 0.001). The median number of RF ablation per patient (sedation group 7 vs GA group 9; P = 0.32) and time to isolation of each vein (sedation group 11 seconds vs GA group 10 seconds; P = 0.9) were similar. Number of acute reconnections requiring further ablations were not significantly different between groups (sedation group 11 [15%] vs GA group 14 [20%]; P = 0.96). One patient sustained transient phrenic nerve injury in the sedation group. Conclusion: Our early experience shows the novel HS balloon ablation can be performed effectively, efficiently and safely under either GA or conscious sedition. The RF balloon ablation catheter paradigm lends itself to refined workflows, with low fluoroscopy requirements and a short learning curve even in initial cohorts.